Human Plasmacytoid Dendritic Cells: From Molecules to Intercellular Communication Network - Mathan, Till S.; Figdor, Carl G.; Buschow, Sonja I. (Frontiers in Immunology, 2013)
Plasmacytoid Dendritic Cells (pDCs) are a specific subset of naturally occurring dendritic cells, that secrete large amounts of Type I interferon and play an important role in the immune response against viral infection. Several studies have highlighted that they are also effective antigen presenting cells (APCs), making them an interesting target for immunotherapy against cancer. However, the modes of action of pDCs are not restricted to antigen presentation and IFN secretion alone. In this review we will highlight a selection of cell surface proteins expressed by human pDCs that may facilitate communication with other immune cells, and we will discuss the implications of these molecules for pDC-driven immune responses.